El liderazgo y la comunicación de la directora y el desarrollo académico de la escuela fiscal de niñas, María Paulina Solís, de la parroquia y cantón Yantzaza, de la provincia de Zamora Chinchipe, durante el período lectivo 2011-2012. Lineamientos alternativos - Pardo Criollo, Eleana Elizabeth (2014)
The present investigation was carried out in the girls’ school tax María Paulina Solis. The problem is: How leadership influences and communication with the Principal, in the academic development of the Maria Paulina Solis school tax in Yantzaza parish and town , in Zamora Chinchipe Province in the academic year 2011- 2012?. The overall objective was: To determine the influence of leadership and communication director of the academic development of the school. Were applied interviews to authorities and surveys to the teachers, students and parents. Information which served to corroborate the hypothesis about the significant influence of leadership and communication with the principal, in the academic development of the Institution. As a result of the research process, we have proceeded to determiner that: The lack of leadership is a problem of importance and concern to the authorities, teachers, parents, students and general community. Aditionally the interpretation of the information, it made possible the construction of the following conclusions: In the María Paulina Solis school tax of Yantzaza, hasn’t exercised a transformational leadership that generates enthusiasm, motivation, nor has encouraged the participation of the involved; they have not promoted fully standars of living in the institution, the teamwork culture has not been completely developed and has affected so decisive in the academic situation of the school, affective treatment has only been eventually given way; in promoting empowerment, it has been sporadically. Instructions that have been given in the institution, they have not been fully affective for all involved. Consistent with the findings, the researcher would like to suggest the following: Authorities must plan, a pedagogical workshop, which allow the managers and all employees, discuss modern theories of transformational leadership; the same that will allow the long term, improve communication leadership and academic development at the institution.